Effects of Elevated CO2 on Maize Physiological and Biochemical Processes - Pirzada Khan; Tariq Aziz; Rahmatullah Jan; Kyung-Min Kim (Agronomy)
Maize (Zea mays) is a critical global crop, serving as a source of food, livestock feed, and industrial raw materials. Climate changes, driven by rising atmospheric carbon dioxide (CO2) levels, have substantial effects on maize physiology, growth, and nutrient content. This review investigates the impact of elevated CO2 on maize, with a particular focus on photosynthesis enhancement as it improves water use efficiency (WUE), which can lead to increased biomass production. Despite this, elevated CO2 results in a decreased concentration of essential nutrients, including nitrogen, phosphorus, potassium, and folate. The reduction in folate, which is vital for both plant development and human nutrition, poses challenges, especially for population heavily reliant on maize. Additionally, biofortification through traditional breeding and genetic engineering is proposed as a strategy to enhance folate level in maize to mitigate nutritional deficiencies. Elevated CO2 stimulates lignin production, improving stress resistance and carbon sequestration capacity. However, the increase in guaiacyl-rich lignin may negatively affect biomass degradability and efficiency in biofuel production. The findings emphasize the importance of balancing maize’s stress resilience, nutrient profile, and lignin composition to address future climate challenges. This balance is essential for optimizing maize cultivation for food security, biofuel production, and environmental sustainability.